Specific tissue reactions after treatment with the valve bronchial block as per the data of pathomorphological examination of the resected material - S. V. Sklyuev; A. V. Levin; E. A. Tseymakh (Туберкулез и болезни лёгких)
The resected material obtained during treatment of destructive pulmonary tuberculosis patients was analyzed, the treatment included bronchial valve block. The majority of patients from comparison group – 23(92.0%) and 6 (40.0%) from the main group (p = 0.0007, Fisher’s exact test – FET) manifested the signs of specific and non-specific pulmonary inflammation at the moment of surgery. Symptoms of chronic bronchitis were detected in 32 (80.8%) patients, of them in 12 (80.0%) in the main group and in 20 (80.0%) patients in the comparison group (p = 0.6, FET). It has been found out that the use of bronchial valve block in the observed patients did not cause the development or exacerbation of chronic bronchitis.